The Influence of the Teaching Assistance Program based on Student Communication Skills and Teamwork Skills - Enjelica, Lovina Kharisma; Mustiningsih, Mustiningsih; Bafadal, Ibrahim (Universitas Negeri Malang, 2024)
The quality of the implementation of Teaching Assistance can be seen from the communication skills and teamwork skills of students after carrying out the activity. The quality of the implementation of Teaching Assistance is good, so students' communication skills improve and the quality of the implementation of Teaching Assistance is good, so teamwork skills increase. The research objectives are: (1) to describe the quality of the implementation of Teaching Assistance; (2) describe the quality of communication skills of students who graduated from Teaching Assistance; (3) describe the quality of teamwork skills of students who graduated from Teaching Assistance; (4) determine the influence of the quality of the implementation of Teaching Assistance on student communication skills; (5) determine the effect of the quality of the implementation of Teaching Assistance on student teamwork skills; (6) determine the effect of the quality of the implementation of Teaching Assistance on students' communication skills and teamwork skills. This research uses quantitative methods which are analyzed using descriptive analysis, simple linear regression analysis, and MANOVA test. The results of this research are (1) the quality of implementation of the Teaching Assistance Program for State University of Malang students is classified as high; (2)the quality of communication skills of students graduating from Teaching Assistance at State University of Malang is classified as high; (3) the quality of teamwork skills of students graduating from Teaching Assistance at State University of Malang is classified as high; (4) there is a significant influence between Teaching Assistance on the communication skills of State University of Malang students; (5) there is a significant influence between Teaching Assistance on the communication skills of State University of Malang students; (6) there is an influence of the Teaching Assistance program on the communication skills and teamwork skills of State University of Malang students. Keywords : teaching assistance; communication skills; teamwork skills